Negative Regulation of miR-375 by Interleukin-10 Enhances Bone Marrow-Derived Progenitor Cell-Mediated Myocardial Repair and Function After Myocardial Infarction. (25th August 2015) - Garikipati, Venkata Naga Srikanth; Krishnamurthy, Prasanna; Verma, Suresh Kumar; Khan, Mohsin; Abramova, Tatiana; Mackie, Alexander R.; Qin, Gangjian; Benedict, Cynthia; Nickoloff, Emily; Johnson, Jennifer; Gao, Ehre; Losordo, Douglas W.; et al.
Abstract: Poor survival and function of transplanted cells in ischemic and inflamed myocardium likely compromises the functional benefit of stem cell-based therapies. We have earlier reported that co-administration of interleukin (IL)−10 and BMPAC enhances cell survival and improves left ventricular (LV) functions after acute myocardial infarction (MI) in mice. We hypothesized that IL-10 regulates microRNA-375 (miR-375) signaling in BMPACs to enhance their survival and function in ischemic myocardium after MI and attenuates left ventricular dysfunction after MI. miR-375 expression is significantly upregulated in BMPACs upon exposure to inflammatory/hypoxic stimulus and also after MI. IL-10 knockout mice display significantly elevated miR-375 levels. We report that ex vivo miR-375 knockdown in BMPAC before transplantation in the ischemic myocardium after MI significantly improve the survival and retention of transplanted BMPACs and also BMPAC-mediated post-infarct repair, neovascularization, and LV functions. Our in vitro studies revealed that knockdown of miR-375-enhanced BMPAC proliferation and tube formation and inhibited apoptosis; over expression of miR-375 in BMPAC had opposite effects. Mechanistically, miR-375 negatively regulated 3-phosphoinositide-dependent protein kinase-1 (PDK-1) expression and PDK-1-mediated activation of PI3kinase/AKT signaling. Interestingly, BMPAC isolated from IL-10-deficient mice showed elevated basal levels of miR-375 and exhibited functional deficiencies, which were partly rescued by miR-375 knockdown, enhancing BMPAC function in vitro and in vivo. Taken together, our studies suggest that miR-375 is negatively associated with BMPAC function and survival and IL-10-mediated repression of miR-375 enhances BMPAC survival and function. Stem Cells 2015;33:3519–3529